IMPLEMENTASI MODEL DDD-E DALAM TRANSFORMASI CERITA RAKYAT MENJADI DIGITAL STORYTELLING: STUDI KASUS DI KELAS XI SMAN 7 BUNGO - Suryasari, Rani; Yusra. D; Priyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is driven by the low engagement and motivation of students in studying traditional literature at SMAN 7 Bungo, where conventional teaching methods often fail to resonate with Generation Z’s digital preferences. The study aims to analyze the implementation of the DDD-E (Decide, Design, Develop, Evaluate) model in the adaptation of local folklore into digital storytelling. Employing a qualitative descriptive approach, the research focuses on how students transform oral traditions, such as the legends of Batu Bangkai and Tanah Periuk, into multimodal digital content. The findings indicate that the systematic stages of the DDD-E model effectively facilitate the adaptation process, enabling students to integrate linguistic narrative with visual and audio elements through AI-assisted tools like Leonardo AI and CapCut. The results show a significant increase in student enthusiasm and digital literacy, as well as a deeper appreciation for local cultural heritage. By bridging traditional folklore with modern technology, this model provides an innovative framework for literature education that is both relevant and interactive. It is concluded that the DDD-E model not only enhances students' creative writing skills but also serves as a strategic medium for preserving local wisdom in the digital era.